Camminando filo di una diagnosi differenziale. Il caso di Mario - Montanaro, Dori (Il sogno della farfalla, 2017)
This work proposes some reflections about the theme of differential diagnosis between primary psychosis and chemically-induced psychosis, mainly at early stages of the disease. Hence, the description of the case history of a patient who, after first compulsory admission and involuntary treatment, was diagnosed with “substance-induced psychotic disorder”. Some of the patient’s clinical features, such as affective flatness and his not really asking for help, together with finding out about a mental health condition at risk which dated back to two years prior to psychotic onset, supported the hypothesis that the patient was affected by primary psychosis rather than a psychosis due to psychotropic substances. In order to distinguish between substance-induced psychosis and primary psychosis, it is therefore fundamental to couple categorical diagnosis with a psychodynamic-type diagnosis which not only takes into account symptoms and behaviour.